Effects of boiling heat transfer on the performance enhancement of a medium speed diesel engine fueled with diesel and rapeseed methyl ester. (25th March 2020) - Zhang, Zhiqing; E, Jiaqiang; Chen, Jingwei; Zhao, Xiaohuan; Zhang, Bin; Deng, Yuanwang; Peng, Qingguo; Yin, Zibin
Graphical abstract: Highlights: An improved heat transfer model with considering boiling is established. Simulation results with and without considering boiling are verified. Performance of diesel engine fueled by rapeseed methyl ester is predicted accurately. Inlet parameters on engine characteristic are investigated by a perturbation method. Abstract: In order to better evaluate the nucleate boiling heat transfer, a new heat transfer model is developed in the AVL-Boost environment. The improved heat transfer model considers the influence of boiling heat transfer in the cylinder-jacket of diesel engine. The combustion process of diesel engine fueled with diesel and rapeseed methyl ester is calculated by an improved chemical kinetics mechanism, which consists of 475 reactions and 134 species. In addition, the effects of boiling heat transfer in cylinder-jacket on performance and emission characteristics of diesel engine are investigated. The result shows that the improved model with considering the boiling heat transfer in the cylinder-jacket agrees better with the experimental result compared with the model without considering the boiling heat transfer. In addition, the perturbation sensitivity analysis of each parameter such as fuel injection pressure, exhaust gas recirculation, injection quantity, injection timing, fuel injection duration, compression ratio, inlet air pressure and inlet air temperature on diesel engine characteristic is investigated by a perturbation method. Finally, the most influential parameter of diesel engine on outputs of diesel engine is investigated and obtained.